Assessment of the effectiveness of the tax burden of the Republic of Kazakhstan - M. S. Dosmanbetova; M. M. Khalitova (Экономика: стратегия и практика)
The aim of the study is to provide theoretical justification and develop practical recommendations in the field of methods for assessing the tax burden and regulating its value, which contributes to the innovative development of the economy. The object of study is the tax burden of subjects of Kazakhstan, considered in the aspect of rationalization in order to stimulate the growth of GRP. The subject of the study is the processes of forming the tax burden, as well as models for assessing its acceptablelevel. Research methods. In the study, various methods were used to obtain, process and analyze the source materials:general scientific methods, methods of economic analysis, mathematical statistics, economic and mathematical modeling. The actual data processing and corresponding calculations were carried out using the Microsoft Excel table processor. The author’s contribution to the study. The author made a contribution to the development of theoretical and methodological provisions, conclusions, scientific and practical recommendations for modeling the impact of the tax burden on GRP and testing the results of the study. The scientific novelty of the study consists in the development of theoretical and methodological provisions for improving the assessment of the tax burden on the economy, taking into account the factors introduced by the reform of the tax system. The practical significance of the study lies in the fact that the theoretical provisions justified in the work, the proposals and recommendations contained in it can be used: by public administration bodies in developing comprehensive measures to build an effective tax system; by tax authorities in order to analyze financial and economic activities and identify factors affecting the level of tax burden and non-fulfillment of tax obligations; by enterprises in the field of tax management and business planning.